STRATEGI PERBANKAN DALAM IMPLEMENTASI GREEN ECONOMY - Febrianto, Gustaf Naufan; Brahmayanti, Ida Ayu Sri (Gapenas Publisher, 2024)
Indonesia has great potential to develop a green economy as a form of environmentally friendly and sustainable development. However, to achieve this goal, support from various parties is needed, including financial institutions such as banks. Although banks in Indonesia have introduced several products and services related to the green economy, the role of banks in encouraging the implementation of the green economy in Indonesia has not been optimal. One of the main obstacles is the lack of awareness and understanding of the green economy among the public and business people. In fact, banks as financial institutions can play an important role in increasing understanding and awareness of the green economy through targeted education programs and campaigns. Banks can also provide financial incentives for business people who implement environmentally friendly and sustainable business practices. The purpose of this study is to find out the Banking Strategy in encouraging the acceleration of the green economy towards economic recovery and multilateral problems. This research is a qualitative descriptive research that uses a type or approach of literature study. The results of this study reveal that in encouraging the implementation of the green economy or green economy, the banking sector has a strategic role, the green economy has a close relationship between economic growth and environmental responsibility that supports each other, In order to strengthen the role of banking in encouraging the acceleration of the implementation of the green economy in Indonesia, strategies that can be applied include strengthening government policies, developing regulations and banking practice standards that sustainability, increasing market demand, technological innovation and banking finance, as well as strengthening partnerships and collaborations with various stakeholders